LANGUAGE AS AN INSTRUMENT OF PATRIARCHAL CONTROL: A FAIRCLOUGH CRITICAL DISCOURSE ANALYSIS OF GENDER IDEOLOGY IN THE WANDIU-DIU FOLKTALE - Sutrah (International Journal of Research on English Teaching and Applied Linguistics, 2026)
Wandiu-diu is a folktale originating from the Wolio community of the Sultanate of Buton, Southeast Sulawesi, Indonesia. While prior scholarship has examined the tale through the lens of Simone de Beauvoir's gender theory, identifying its construction of women as wives, mothers, and independent figures, no study has yet applied Norman Fairclough's Critical Discourse Analysis (CDA) three-dimensional model to systematically expose the linguistic mechanisms through which patriarchal ideology is produced and reproduced. This article addresses that gap by analysing the folktale text at three interlocking levels: (1) the textual dimension, through transitivity analysis, imperative verb structures, possessive pronoun use, and evaluative lexis; (2) the discursive practice dimension, examining the production, distribution, and consumption of the written text as documented by Rasyid (1998) under the Indonesian state's language authority; and (3) the sociocultural practice dimension, situating the tale within the patriarchal structures of Butonese adat and the Sultanate of Buton. Analysis reveals that the folktale systematically constructs women as grammatical objects rather than active subjects, instrumentalises the mother's body as a site of violence and punishment, and deploys symbolic transformation, the mother's metamorphosis into a mermaid, not as liberation but as the ultimate patriarchal sanction against female defiance. The institutionalised documentation of the tale further amplifies its ideological weight by projecting one particular version as an authoritative cultural heritage text. These findings contribute to the growing body of CDA research on gender in Indonesian oral literature by revealing the precise discursive mechanisms through which patriarchal control operates in the narrative.